The Behavior of Consumers and Producers of Food of Animal Origin and Their Impacts in One Health - Nespolo, Natália Maramarque (Frontiers in Veterinary Science, 2021)
Most people consume animal foods, for example meats, but few are concerned with the quality and origin of these products. Many studies point out hygiene problems of these foods after production, however the lack of knowledge of the consumers of animal products about the importance of hygienic-sanitary control during the production process, can lead them to a bad choice when buying these products and, consequently, expose themselves to the risk of acquiring many diseases, such as zoonosis. In this perspective, the objective of this work is to reflect about the consumers’ role in the production of safe food of animal origin and to show that the population’s health education is necessary and urgent. Only by helping the consumers to obtain knowledge about the production of animal products origin there will be a change in consumption habits, preventing the ingestion of contaminated foods that can cause damage to human health and to the environment, consequently, promoting the one health.